PARTICIPATION IN TEACHING PRESCHOOL CHILDREN LEARNING SPEECH, THINKING AND COMMUNICATING - Isabayeva Asida Yusufjonovna (Scholar Express Journal, 2022)
This article focuses on children’s speech development. It describes concepts such as listening, thinking, and communication, which are key factors in the development of preschool children’s speech, and provides a scientific basis for the development of children's speech as a result of their interdependence
Keywords: Speech development; listening; attention; mindfulness